PBK Enhances Cellular Proliferation With Histone H3 Phosphorylation and Suppresses Migration and Invasion With CDH1 Stabilization in Colorectal Cancer - Koshino, Akira; Nagano, Aya; Ota, Akinobu; Hyodo, Toshinori; Ueki, Akane; Komura, Masayuki; Sugimura-Nagata, Akane; Ebi, Masahide; Ogasawara, Naotaka; Kasai, Kenji; Hosokawa, Yoshitaka; Kasugai, Kunio; et al. (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is one of the most frequent gastrointestinal malignancies with high morbidity and mortality rates. Several biological markers for the prognostication of patient outcome of CRCs are available. Recently, our group identified two favorable factors for the survival of CRC patients: PDZ-binding kinase (PBK) and phospho-histone H3 (PHH3). Both showed a significant inverse association to pT stage. The aim of this study was to uncover the mechanism through which these cellular proliferation–associated protein expressions lead to favorable clinical outcome in CRC patients. We first confirmed co-expression of PBK and PHH3 in CRC cells. Further investigation showed that aberrantly expressed PBK up-regulated the cellular proliferation of CRC cells with accumulation of PHH3. The PBK inhibitor OTS514 suppressed cellular proliferation of CRC cells through down-regulation of PHH3 and induction of apoptosis. In vitro studies revealed that PBK suppressed the migration and invasion of CRC cells with suppression of Wnt/-catenin signaling with CDH1 stabilization. Exogeneous PBK up-regulated the phosphorylated CDH1 at S840, S846, and S847 residues in cultured cells. Recombinant PBK directly phosphorylated HH3; however, it failed to phosphorylate CDH1 directly in vitro. The present study demonstrated the association of two markers PBK and PHH3 in CRC. We further identified one of the potential mechanisms by which higher expression of these cellular proliferation–associated proteins leads to the better survival of CRC patients, which likely involves PBK-mediated suppression of the migration and invasion of CRC cells. Our findings suggest that PBK-targeting therapeutics may be useful for the treatment of CRC patients with PBK-expressing tumors.